1999
DOI: 10.1037/0735-7028.30.5.519
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of the EPPP: How do licensure candidates view the process?

Abstract: A common bond of licensed psychologists is taking the Examination for Professional Practice in Psychology (EPPP). The authors discuss how test takers feel about the EPPP as a basis for entry into the profession of psychology. Reasons for perceptions are discussed and suggestions for creating more positive perceptions are provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
28
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 51 publications
4
28
0
Order By: Relevance
“…A variety of perceptions have been studied to date, including procedural justice (e.g., Bauer, Truxillo, Sanchez, Craig, Ferrara, & Campion, 2001;Ployhart & Ryan, 1998), distributive justice (e.g., Smither et al, 1993), interpersonal justice (e.g., Ryan & Chan, 1999), informational justice (e.g., Bauer, Maertz, Dolen, & Campion, 1998), test motivation (e.g., Sanchez, Truxillo, & Bauer, 2000), test anxiety (e.g., Ryan, Ployhart, Greguras, & Schmit, 1998), attitudes towards tests in general (e.g., Chan, Schmitt, Jennings, Clause, & Delbridge, 1998), and attitudes towards selection in general (e.g., Macan et al, 1994). The justice perspective stems directly from Gilliland (1993) who proposed that applicants' perceptions of fairness directly influence subsequent attitudes and behaviors both during and after hiring.…”
Section: Applicant Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of perceptions have been studied to date, including procedural justice (e.g., Bauer, Truxillo, Sanchez, Craig, Ferrara, & Campion, 2001;Ployhart & Ryan, 1998), distributive justice (e.g., Smither et al, 1993), interpersonal justice (e.g., Ryan & Chan, 1999), informational justice (e.g., Bauer, Maertz, Dolen, & Campion, 1998), test motivation (e.g., Sanchez, Truxillo, & Bauer, 2000), test anxiety (e.g., Ryan, Ployhart, Greguras, & Schmit, 1998), attitudes towards tests in general (e.g., Chan, Schmitt, Jennings, Clause, & Delbridge, 1998), and attitudes towards selection in general (e.g., Macan et al, 1994). The justice perspective stems directly from Gilliland (1993) who proposed that applicants' perceptions of fairness directly influence subsequent attitudes and behaviors both during and after hiring.…”
Section: Applicant Reactionsmentioning
confidence: 99%
“…Perceived procedure characteristics include many of the justice rules identified by Gilliland (1993) such as job relatedness, opportunity to perform, reconsideration opportunity, two-way communication, and propriety of questions (e.g., Bauer et al, 1998;Ryan & Chan, 1999;Truxillo et al, 2001). In particular, job relatedness has been studied extensively in previous research based on the premise that applicants will perceive selection more favorably to the extent that techniques are perceived as face valid and predictive of job performance.…”
Section: Applicant Reactionsmentioning
confidence: 99%
“…Although the nature of postdoctoral requirements varies from state to state, nearly all jurisdictions call for (a) a minimum number of supervised training hours, (b) successful completion of the national Exam for the Professional Practice of Psychology (EPPP), and (c) the passing of additional state-specifi c oral and/or written exams. Regardless of the career path chosen, graduates may struggle to fi nd postdoctoral experiences that will allow them to meet licensure requirements (Olvey, Hogg, & Counts, 2002;Ryan & Chan, 1999). However, those seeking tenure-track positions in clinical or counseling psychology doctoral programs accredited by the American Psychological Association (APA) may encounter unique challenges in the pursuit of licensure.…”
mentioning
confidence: 99%
“…High failure rates do not, of course, constitute a prima facia reason to presume that the exam is not serving its intended purpose; the failure rate for the EPPP is comparable with that for the bar exam (33% in 2007), which also determines eligibility for a broad, generic license to practice. Still, as Sharpless and Barber have noted, examinees report weak confidence in the validity and fairness of the test (Ryan & Chan, 1999), which adds to the perception that psychology has constructed unreasonable barriers to entry into the profession (Olvey, Hogg, & Counts, 2002). Until it can be demonstrated that the EPPP is associated with some relevant performance criterion, the exam and its developers remain vulnerable to charges that it is an arbitrary obstacle serving the professional guild more than the consumer.…”
mentioning
confidence: 99%